Stem Cell Therapy for Men’s Vitality in Supporting National Health and Defense: A Comprehensive Review and Meta-Analysis - Deby Susanti Pada Vinski; Svetlana Trofimova; Prihati Pujowaskito; Markus Wibowo; Natasha Cinta Vinski (Riviera Publishing, 2025)
This comprehensive review and meta-analysis examines the efficacy of stem cell therapy in enhancing men’s vitality while supporting national health and defense systems. Patient care records served as the primary source of data for evaluation and analysis, ensuring that real-world clinical outcomes were robustly captured. The study also evaluated the quality assurance of stem cell products cultured by the integrated Celltech Stem Cell Centre Laboratory and Banking, affirming that these products meet stringent clinical standards. Findings indicate that stem cell therapy possesses significant regenerative potential, particularly in repairing damaged cells. Notably, several patients who underwent therapy at the Celltech Stem Cell Center experienced remarkable functional recovery. These results underscore the therapeutic promise of stem cells not only for individual patient recovery but also as a strategic component in enhancing overall public health and national defense readiness.